E-121 Salvage endovascular strategies in a unique duplicated internal carotid artery leading to catastrophic dissection and fusiform aneurysm. (4th August 2020) - Lodi, Y; Pulgarin, B; Weiss, Z; Chin, S; Reddy, V
Abstract : Background: Anatomical variance of duplicated internal carotid artery (ICA) is novel. However, duplication associated dissecting stenosis in one lumen and fusiform aneurysm in second lumen is not described. Objective: To report a case of ICA dissection originating from a duplicated ICA that caused an intracranial occlusion and extracranial fusiform aneurysm. Additionally, we report our endovascular salvage strategies. Case: A 41-year-old woman with history of hypertension and migraines presented with worsening headaches. Angiography demonstrated left ICA dissection without critical stenosis, but small pseudoaneurysm, patient was managed conservatively. Follow-up MRA required for worsening symptoms, showed deteriorating dissecting-narrowing at the skull-base in the petrous ICA. Emergent angiography revealed a dissecting long segment lesion extending from the distal cervical carotid artery to the petrous segment with critical stenosis of 90%. Duplicated ICA originated 20 mm from the ICA origin and ended at C2 level meeting the original ICA from where the dissection began. The other duplication demonstrated a fusiform dilation at the center. Petrous ICA was repaired by PTA followed by Neuroform EZ stent and distal cervical ICA was reconstructed with additional 3 Neuroform Allas stents. Despite reconstruction, antegrade flow to the ICA remained slow due to the competitive flow from other duplications. Emergent shut-down of the fusiform duplication obtained by embolizing 3 large Stryker XL coils resulting in restoration of antigrade flow to the stented segments. Patient remained neurologically intact and discharged home in 2 days. Conclusions: Carotid duplication may lead to dissection and fusiform aneurysm formation. Competitive flow from duplication may responsible for dissection. Sacrifice of one of the duplication of the ICA, especially, the fusiform one is needed to maintain persistent antigrade flow. Disclosures: Y. Lodi: None. B. Pulgarin: None. Z. Weiss: None. S. Chin: None. V. Reddy: 2; C; Terumo. 3; C; Janssen, Chiesi Inc, Portola.